Revision of genus Texoreddellia Wygodzinsky, 1973 (Hexapoda, Zygentoma, Nicoletiidae), a prominent element of the cave-adapted fauna of Texas - Espinasa, Luis; Bartolo, Nicole D.; Centone, Danielle M.; Haruta, Charisse S.; Reddell, James R. (Zootaxa, 2016)
While many cave-adapted organisms tend to be endemic to single locations or restricted to single karstic regions, the troglobitic silverfish insects of genus Texoreddellia can be found in scores of different cave localities that cover a range of nearly 160,000 km2. They are among the most important and common representatives of the cave-adapted fauna of Texas and Coahuila, in northern Mexico. Using morphological and mitochondrial gene sequence data, we have corroborated the presence of at least six different species within the genus and provided species identifications to populations inhabiting 153 different cave locations. Results show that species ranges are larger than previously reported and that ranges tend to greatly overlap with each other. We have also found that different species of Texoreddellia commonly inhabit the same cave in sympatry. Data supports that some species of Texoreddellia can easily disperse through the extensive network of cracks, fissures and smaller cavities near the surface and epikarst.